LiF-SiO / C composite material as well as preparation method and application thereof

The three-dimensional LiF-SiO/C composite material prepared by freeze-drying combined with heat treatment process solves the problem of low Coulomb efficiency in lithium-ion batteries in the first week, achieving higher electrochemical performance and more stable battery performance.

CN119560519APending Publication Date: 2025-03-04HUNAN INSTITUTE OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411476648.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Traditional graphite anode materials cannot meet the demand for maximum energy density of energy storage devices by electric vehicles. The inactive lithium silicate formed by SiO in lithium-ion batteries leads to low Coulomb efficiency in the first week, and the formation of solid electrolyte interface (SEI) consumes a large amount of electrolyte and active lithium.

Method used

Through a heat treatment process combined with freeze-drying, a three-dimensional LiF-SiO/C composite material was prepared, and a uniform LiF passivation layer was synthesized in situ by gas-phase fluorination, and the ratio of SiO and LiOH·H2O was adjusted to obtain appropriate crystallinity and lithium supplementation effect. SiO particles were evenly wrapped in a porous honeycomb conductive carbonaceous network structure.

Benefits of technology

It improves the conductivity, promotes the transmission of ions and electrons, alleviates volume changes, improves the problem of low first-term efficiency, and enhances the electrochemical performance of the negative electrode material of lithium-ion battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560519A_ABST
    Figure CN119560519A_ABST
Patent Text Reader

Abstract

The invention discloses a LiF-SiO / C composite material as well as a preparation method and application thereof. Commercial SiO particles are selected, LiOH.H2O and sodium chloride are added, lithium-supplemented SiO is packaged in a honeycomb porous carbon matrix network through freeze drying, an obtained sample is calcined in protective gas, meanwhile, a SiO / C composite material is fluorinated through a chemical vapor phase method, and then the carbon-coated LiF passivation layer SiO composite material is obtained through water washing. The method is convenient and easy to operate and controllable in reaction condition, the initial effect of the obtained porous carbon coated uniform LiF passivation layer SiO composite material is improved through lithium supplement, the characteristic of large specific surface area of porous carbon is beneficial to full contact of an electrolyte and an active substance, volume expansion of the material in the charging and discharging process is effectively relieved through carbon coating and the uniform LiF passivation layer, and the performance of the material is improved. When the silicon-carbon composite material is used as a lithium ion battery negative electrode material, the electrochemical performance of the lithium ion battery negative electrode material is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery negative electrode materials, and in particular to a LiF-SiO / C composite material and a preparation method and application thereof. Background Art

[0002] The electric vehicle market is currently increasing its demand for maximizing the energy density of energy storage devices, but the capacity of traditional graphite anodes cannot meet this demand. Due to its ultra-high theoretical capacity, moderate volume expansion, and low working potential, SiO is considered a potential candidate for lithium-ion battery anode materials.

[0003] However, SiO can form bulk inactive lithium silicate (Li2Si n O 2n+1 ). Although Li2Si n O 2n+1 As a matrix, it can alleviate the volume change, but its irreversibility will lead to the loss of active lithium, resulting in a low first-cycle coulombic efficiency (ICE). The formation of the solid electrolyte interface (SEI) will also consume a large amount of electrolyte and active lithium. It is well known that low ICE has a crucial impact on the energy density and cycle life of the battery, especially the full battery. Pre-lithiation is considered to be the most effective way to compensate for the loss of active lithium, thereby improving the ICE. Therefore, if the first efficiency of SiO can be improved by lithium supplementation, the carbon coating and LiF passivation layer can reduce the volume expansion of SiO, promote the continuous generation of a stable SEI film, enhance its electrochemical performance, and meet the requirements of commercial applications. Developing simple and reasonable modification strategies to optimize the electrochemical properties of silicon anode materials is an important research direction for the application of lithium-ion battery anodes.

[0004] In the present invention, for the first time, a three-dimensional LiF-SiO / C structure can be prepared by freeze-drying combined with a heat treatment process without destroying the microstructure of the material. The final product uniformly wraps SiO particles with a uniform LiF passivation layer in a porous honeycomb conductive carbon network structure, which can not only improve the conductivity and promote the transmission of ions and electrons, but also alleviate the drastic volume change and improve the problem of low initial efficiency. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a carbon matrix encapsulated SiO composite material with a uniform LiF passivation layer and its preparation and application. The present invention can obtain a three-dimensional LiF-SiO / C structure, and at the same time, SiO with a suitable crystallinity can be obtained by adjusting the ratio of SiO and LiOH·H2O during the preparation process, and lithium-supplemented SiO can be obtained by adding LiOH·H2O. The SiO composite material with a uniform LiF passivation layer is synthesized in situ by gas phase fluorination, and the material is used for the negative electrode of a lithium ion battery, which has excellent electrochemical performance.

[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is:

[0007] A method for preparing a LiF-SiO / C composite material comprises the following steps:

[0008] (1) adding the polymer to deionized water and stirring evenly to obtain a viscous clear liquid A;

[0009] (2) Add SiO, LiOH·H2O and NaCl to solution A in proportion and stir evenly to obtain a viscous brown solution B;

[0010] (3) The viscous brown solution B is freeze-dried, and the obtained product is placed in a fluoride under a protective atmosphere for heat treatment to obtain a carbon matrix-encapsulated SiO composite material with a LiF passivation layer.

[0011] The polymer in step (1) is a high molecular weight organic substance, including one or more of polyvinyl pyrrolidone (PVP, Mw = 1300000) and polyvinyl alcohol (PVA, Mw = 67000), preferably polyvinyl alcohol (PVAMw = 67000).

[0012] The liquid-to-solid ratio in step (1) is 8-15 ml / g, preferably 10 ml / g.

[0013] In step 2), commercial SiO with a particle size of 1 to 2 μm is used, which is obtained by ball milling commercial SiO with a particle size of 4 to 6 μm for 50 to 70 minutes.

[0014] The mass ratio of SiO to polymer in step (2) is 1:8 to 1:12, preferably 1:10.

[0015] The mass ratio of NaCl to polymer in step (2) is 1:0.9 to 1:1.1, preferably 1:1.

[0016] In step (2), the mass ratio of LiOH·H2O to SiO is 1:100 to 2:100; preferably: 1:100.

[0017] The freeze-drying cold trap temperature in step (3) is -40 to -96°C, and the time is 20 to 30 hours; preferably -62°C; and the time is 24 hours.

[0018] The molar ratio of NH4F or PVDF to LiOH·H2O in step (3) is 0.5:1 to 2:1, preferably 1:1.

[0019] The heat treatment temperature under protective atmosphere in step (3) is 700-900° C., and the heat treatment time is 2-4 h; preferably 800° C.; the heat treatment time is 2 h.

[0020] Step (3) is preferably: placing the freeze-dried sample into a tubular furnace, placing NH4F or PVDF at the front end of the tubular furnace pipe ventilation, and performing heat treatment under a protective atmosphere of N2 or Ar.

[0021] The present invention also provides a LiF-SiO / C composite material, which is prepared by the above-mentioned preparation method.

[0022] The present invention also provides application of the LiF-SiO / C composite material in preparing anode materials for batteries.

[0023] The honeycomb carbon matrix LiF passivation layer described in the present invention is obtained by freeze-drying a conductive polymer solution and heating a fluoride. The present invention finds that gas-phase fluorinated LiOH can form a uniform LiF distribution in situ on the SiO surface. Direct addition of LiF and SiO ball mill mechanical mixing easily forms agglomerated LiF with discrete distribution, which affects the stable construction of SEI. The crystallinity of SiO varies with the ratio of LiOH·H2O and SiO. With appropriate crystallinity, the shell is conducive to lithium ion transmission and effectively inhibits volume expansion. However, excessive crystallinity produces an electrochemically inert phase c-SiO2, which reduces the reversible capacity of the material and hinders the transmission of lithium ions, which is harmful to the multiplication and cycle performance of the battery. LiF-SiO / C-1 (the mass ratio of LiOH·H2O to SiO is 1%) provides up to 637.3mAh g -1 The reversible capacity of 200 cycles at 1Ag -1 The relevant conclusions can be found in Figure 3 , Figure 4 , Figure 5 .

[0024] Compared with the prior art, the advantages of the present invention are:

[0025] 1. The present invention has simple raw materials, short process flow and is environmentally friendly;

[0026] 2. The present invention adopts freeze-drying method for direct synthesis, the process is simple and easy, and the dried material maintains the original chemical composition and physical properties;

[0027] 3. The product synthesized by the present invention has a special structure, a porous network structure, and a large number of SiO particles are encapsulated inside, with a large specific surface area and a stable structure;

[0028] 4. Through heat treatment under a protective atmosphere, fluoride gas phase fluorination supplements lithium SiO, which is more evenly distributed than directly adding LiF and is less likely to agglomerate. The LiF passivation layer can serve as part of the solid electrolyte interface film (SEI), which helps to improve the cycle stability and safety of the battery, thereby enhancing the overall performance of the battery.

[0029] 5. The product synthesized by the present invention has uniform morphology distribution and large specific surface area, which is beneficial to improving the electrochemical performance when used as negative electrode material for lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a SEM picture of commercial SiO obtained in Example 1 of the present invention;

[0031] Figure 2 1 is a SEM and element distribution picture of the LiF passivation layer SiO / honeycomb carbon matrix composite material obtained in Example 2 of the present invention.

[0032] Figure 3 It is the XRD picture of the LiF passivation layer SiO / honeycomb carbon matrix composite material obtained in Example 2, Example 3 and Comparative Example 1 of the present invention.

[0033] Figure 4 It is a picture of the electrochemical performance of the LiF passivation layer SiO / honeycomb carbon matrix composite material obtained in Example 2, Example 3 and Comparative Example 1 of the present invention.

[0034] Figure 5 It is a comparison picture of element distribution between Example 2 of the present invention and Comparative Example 2.

[0035] Figure 6 This is a comparison picture of the electrochemical properties of the composite materials obtained in Example 2 of the present invention and Comparative Example 2. DETAILED DESCRIPTION

[0036] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0037] Embodiment 1:

[0038] The SiO with a particle size of 4 to 6 μm was milled at 500 rpm using a planetary ball mill for 1 h to obtain SiO with a particle size of 1 to 2 μm. The obtained samples were analyzed using a Japanese Rigaku D / max-2500 X-ray diffraction analyzer. A scanning electron microscope Nova Nano SEM230 from FEI Company of the United States was used. Figure 1 shown.

[0039] Embodiment 2:

[0040] SiO with a particle size of 4-6μm was ball-milled at 500rpm using a planetary ball mill for 1h to obtain SiO with a particle size of 1-2μm. 3g PVA was added to 30ml of ionized water and stirred evenly to obtain a clear solution A. 0.3g SiO, 0.003g LiOH·H2O and 3g NaCl were added to solution A and stirred evenly to obtain a viscous solution B. The viscous solution B was freeze-dried (-62℃, 100Pa, 24h) to obtain product A. Product A was placed in a tubular furnace, and 0.003g NH4F powder was placed at the front end of the tubular furnace pipe and heat-treated at 800℃ for 2h in an argon atmosphere. The product was washed with water to obtain a LiF passivation layer SiO / honeycomb carbon matrix composite material (LiF-SiO / C-1). The obtained sample was analyzed using a Japanese Rigaku D / max-2500 X-ray diffraction analyzer, and the results are shown in the figure. Figure 3 The samples were observed using a NovaNano SEM 230 scanning electron microscope from FEI, USA. Figure 2 As shown. The element mapping results show that the F element is evenly distributed in the carbon framework network. The prepared LiF passivation layer SiO / honeycomb carbon matrix composite material was mixed evenly according to 80wt.% of active material, 10wt.% of Super-P and 10wt.% of PVDF to make a slurry, which was evenly coated on copper foil and assembled into button cells after vacuum drying for electrochemical performance testing. The cycle performance test voltage range was 0.005~1.5V, and the current density was 1A g -1 After 150 cycles, the discharge capacity can reach 643.7 mAh g -1 The cycle performance results are as follows: Figure 4 As shown, it reflects good electrochemical performance.

[0041] Embodiment 3:

[0042] SiO with a particle size of 4-6 μm was ball-milled at 500 rpm for 1 h to obtain SiO with a particle size of 1-2 μm. 3 g PVA was added to 30 ml ionized water and stirred evenly to obtain a clear solution A. 0.3 g SiO, 0.015 g LiOH·H2O and 3 g NaCl were added to solution A and stirred evenly to obtain a viscous solution B. Viscous solution B was freeze-dried (-62°C, 100 Pa, 24 h) to obtain product A, which was placed in a tube furnace, and 0.013 g NH4F powder was placed at the front end of the tube furnace pipe and heat-treated at 800°C in an argon atmosphere for 2 h, and then washed with water to obtain a LiF passivation layer SiO / honeycomb carbon matrix composite material (LiF-SiO / C-5). The sample was observed using a Nova Nano SEM 230 scanning electron microscope from FEI Company of the United States, and it was found that the composite material was composed of a fiber network, showing a multi-layer porous structure, and the SiO particles were well coated therein. The prepared LiF passivation layer SiO / honeycomb carbon matrix composite material was mixed evenly according to 80wt.% of active material, 10wt.% of Super-P and 10wt.% of PVDF to make a slurry, which was evenly coated on copper foil, and assembled into button cells after vacuum drying for electrochemical performance testing. The cycle performance test voltage range was 0.005~1.5V, and the current density was 1A g -1 After 150 cycles, the discharge capacity can reach 324 mAh g -1 The cycle performance results are as follows: Figure 4 shown.

[0043] Comparative Example 1:

[0044] SiO with a particle size of 4-6 μm was ball-milled at 500 rpm using a planetary ball mill for 1 h to obtain SiO with a particle size of 1-2 μm. 3 g of PVA was added to 30 ml of deionized water and stirred evenly to obtain a clear solution A. 0.3 g of SiO and 3 g of NaCl were added to solution A and stirred evenly to obtain a viscous solution B. The viscous solution B was freeze-dried (-62°C, 100 Pa, 24 h) to obtain product A, which was placed in a tubular furnace and heat-treated at 800°C for 2 h in an argon atmosphere, and washed with water to obtain a SiO / honeycomb carbon matrix composite material (SiO / C). The obtained sample was analyzed using a Japanese Rigaku D / max-2500 X-ray diffraction analyzer, and the results are shown in the figure. Figure 3 As shown. The prepared SiO2 / honeycomb carbon matrix composite material was mixed evenly according to 80wt.% of active material, 10wt.% of Super-P and 10wt.% of PVDF to make a slurry, which was evenly coated on copper foil and assembled into button cells after vacuum drying for electrochemical performance testing. The cycle performance test voltage range was 0.005~1.5V, and the current density was 1A g -1After 150 cycles, the discharge capacity is 188 mAh g -1 The cycle performance results are as follows: Figure 4 shown.

[0045] Comparative Example 2:

[0046] 4-6μm SiO and LiF were mixed into powder, wherein the weight percentage of LiF in the powder was 1%. The mixed powder (2.5 g) and ethanol (20 ml) were added to a ball mill with a ball-to-powder ratio of 20:1, and ball milled at 200 rpm for 12 hours. Then, the ethanol was evaporated to dryness, 0.5 g of asphalt was added to the ball mill as a carbon source, and ball milled at 400 rpm for 4 hours. The obtained mixture was heated at 800°C for 2 hours in a nitrogen atmosphere for high-temperature carbonization, and dried to obtain the final product. The prepared SiO / honeycomb carbon matrix composite material doped with LiF was mixed evenly according to 80wt.% of active material, 10wt.% of Super-P and 10wt.% of PVDF to make a slurry, which was evenly coated on a copper foil, and assembled into a button cell after vacuum drying for electrochemical performance testing. The cycle performance test voltage range was 0.005-1.5V, and the current density was 1A g -1 The cycle performance results are as follows Figure 6 shown. Figure 5 3 is a comparison picture of element distribution between Example 2 of the present invention and Comparative Example 2. In the picture, a and b are Example 2, and c and d are Comparative Examples. It can be seen that the distribution of F element in Example 2 is much more uniform than that in the Comparative Example, and the agglomeration of F element in the Comparative Example is more obvious.

Claims

1. A method for preparing a LiF-SiO / C composite material, characterized in that: The following steps are involved: (1) adding the polymer to deionized water and stirring evenly to obtain a viscous clear liquid A; (2) Add SiO, LiOH·H2O and NaCl to solution A in proportion and stir evenly to obtain a viscous brown solution B; (3) The viscous brown solution B is freeze-dried, and the obtained product is placed in a fluoride under a protective atmosphere for heat treatment to obtain a carbon matrix-encapsulated SiO composite material with a LiF passivation layer.

2. The method for preparing a composite material according to claim 1, characterized in that: The polymer in step (1) is a high molecular weight organic substance, including one or more of polyvinyl pyrrolidone (PVP, Mw=1300000) and polyvinyl alcohol (PVA, Mw=67000).

3. The method for preparing a composite material according to claim 1, characterized in that: The liquid-to-solid ratio in step (1) is 8-15 ml / g.

4. The method for preparing a composite material according to claim 1, characterized in that: The mass ratio of SiO to polymer in step (2) is 1:8 to 1:12; The mass ratio of NaCl to polymer in step (2) is 1:0.9 to 1:1.

1.

5. The method for preparing a composite material according to claim 1, characterized in that: In step (2), the mass ratio of LiOH·H2O to SiO is 1:100 to 2:

100.

6. The method for preparing a composite material according to claim 1, characterized in that: The freeze-drying cold trap temperature in step (3) is -40 to -96°C and the time is 20 to 30 hours.

7. The method for preparing a composite material according to claim 1, characterized in that: The fluoride in step (3) includes at least one of NH4F and PVDF, and the molar ratio of the fluoride to LiOH·H2O is 0.5:1 to 2:

1.

8. The method for preparing a composite material according to claim 1, characterized in that: The heat treatment temperature under the protective atmosphere in step (3) is 700-900° C., and the heat treatment time is 2-4 hours.

9. A LiF-SiO / C composite material, characterized in that: The method is prepared according to any one of claims 1 to 8.

10. Use of the LiF-SiO / C composite material according to claim 9 in preparing anode materials for batteries.